Metabolite profiling, antimalarial potentials of Schleichera oleosa using LC-MS and GC-MS: in vitro, molecular docking and molecular dynamics - Vanaja, Peetha; Moorthy, N. S. Hari Narayana; Rajpoot, Vivek Singh; Rao, Harshawardhan; Goswami, Rohit Kumar; Subash, Paranthaman; Khute, Sulekha; Rao, Kareti Srinivasa (Frontiers in Molecular Biosciences, 2025)
PurposeTo explore the phytochemical composition of Schleichera oleosa bark and evaluate its potential antimalarial activity through in vitro and in silico analyses.MethodsThe bark of S. oleosa was subjected to Soxhlet extraction using petroleum ether, chloroform, and methanol. The quantitative analysis of the extracts was performed to determine total phenolic, flavonoid, and tannin contents. Advanced analytical techniques such as Gas Chromatography-Mass Spectrometry (GC-MS) and Liquid Chromatography-Mass Spectrometry (LC-MS) were employed to identify 175 phytoconstituents from the methanolic extract In-vitro antimalarial activity was assessed against Plasmodium falciparum using the candle jar method, measuring parasite growth inhibition. The inhibitory concentration (IC50) values were calculated and compared with standard antimalarial drugs, chloroquine and quinine. Furthermore, computational analyses, including molecular docking and molecular dynamics simulations, were conducted to evaluate the interactions of identified phytochemicals with key malarial targets (1CEQ and 4ZL4). The efficacy of these compounds was compared with standard drugs like artesunate and chloroquine. Additionally, ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) profiling and drug-likeness assessments were performed.ResultsThe methanolic extract of S. oleosa exhibited promising in-vitro antimalarial activity with an average IC50 value of 0.780 μg/mL, which, while higher than chloroquine (0.020 μg/mL) and quinine (0.268 μg/mL), still demonstrated significant efficacy. GC-MS and LC-MS analyses identified 175 phytoconstituents, among which two novel lead compounds, scillarenin and 4-[(Z)-(6-hydroxy-3-oxo-1-benzofuran-2(3H)-ylidene) methyl] phenyl beta-Dglucopyranoside, exhibited the highest docking scores and favorable ADMET profiles. Molecular docking and dynamics simulations confirmed strong binding affinities to malarial targets, surpassing some standard drugs in efficacy.ConclusionThis study reports, for the first time, the antimalarial potential of bioactive constituents derived from the bark of S. oleosa. The identified compounds, scillarenin and 4-[(Z)-(6-hydroxy-3-oxo-1-benzofuran-2(3H)-ylidene) methyl] phenyl beta-D-glucopyranoside, demonstrated promising antiplasmodial activity, validating traditional medicinal claims. The findings highlight the potential of S. oleosa as a source of novel antimalarial agents with fewer side effects compared to existing therapies. Further in vivo studies are warranted to confirm these results and support the development of new antimalarial drugs. This groundbreaking discovery contributes to the growing evidence supporting the role of medicinal plants in drug discovery.